Embodied Female Experience Through the Lens of Imagination - Green, Sharon R. (Journal of Analytical Psychology, 2010)
In 1971, I made a film entitled Self Portrait of a Nude Model Turned Cinematographer in which I explore the objectifying ‘male’ gaze on my body in contrast to the subjective lived experience of my body. The film was a radical challenge to the gaze that objectifies woman – and thus imprisons her – which had hitherto dominated narrative cinema. Since the objectification of women has largely excluded us from the privileged phallogocentric discourses, in this paper I hope to bring into the psychoanalytic dialogue a woman's lived experience. I will approach this by exploring how remembering this film has become a personally transformative experience as I look back on it through the lens of postmodern and feminist discourses that have emerged since it was made. In addition, I will explore how this process of imaginatively looking back on an artistic creation to generate new discourses in the present is similar to the transformative process of analysis. Lastly, I will present a clinical example, where my embodied countertransference response to a patient's subjection to the objectifying male gaze opens space for a new discourse about her body to emerge.
Keywords: 1-Cinéma; 2-Genre et sexualité; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; _Nettoyé